Storage and Condition of Biomass Influence to Biosorption of Lead (II) and Zinc(II) by Saccharomyces cerevisiae Biomass - Jasmidi Jasmidi; Eko Sugiharto; Mudjiran Mudjiran (Indonesian Journal of Chemistry, 2001)
The influence of length and condition of Biomass Storage on the biosorption of lead and zinc that present together in a solution by Saccharomyces cerevisiae biomass were studied. In this experiment, variables of length and condition of biomass storage were examined. Concentration of lead and zinc were determined by atomic absorption spectrophotometric (AAS) using air-acetilene as atomizing flame. Loading of lead and zinc on the biomass were determined as the difference between the initial and the final concentration of lead and zinc in the solution. Biosorption of lead and zinc were influenced by condition and storage of the biomass. Storage of biomass in the room temperature for one week cause an increasing uptake. Storage for longer period result in decrease of lead and zinc uptake. Storage of biomass in a freezer up to 2 weeks increased the uptake of lead, but did not influence the uptake of zinc. Storage for longer period decreased the uptake of both of lead and zinc. For all condition the uptake of lead higher than the uptake of zinc by Saccharomyces cerevisiae.